The Development of Disciplinary Control Book for Elementary School Students - Rahmawati, Puji; Jerusalem, Mohammad Adam; Lidyasari, Aprilia Tina (Mimbar Sekolah Dasar, 2018)
This study was aimed to create a disciplinary control book for elementary school students to control student discipline. This research is a developmental research based on the developmental model of Borg and Gall. Product feasibility was obtained through validation activities from material and media experts. The validation results of media experts showed an average score of 3.75, and material experts showed an average score of 3.15. This score was classified in good category, so that the disciplinary control book products were worth testing for elementary school students. Product feasibility trials were carried out through initial trial and limited field trials. While the assessment of product effectiveness was carried out through extensive field test activities. The results of the initial field trial, small group trial, and field test showed that students' discipline increased after being controlled by using disciplinary control books with a good average score category. Thus, it can be concluded that the disciplinary control book of elementary school students is feasible and effective in controlling elementary school students’ discipline.